Understanding the Determinants of m-Health Adoption in Indonesia - Vivianti Kwee; Istijanto Istijanto; Handyanto Widjojo (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: Mobile health (m-health) is a fast-growing service that enables users to consult with doctors remotely. This research investigates the factors influencing m-health adoption in Indonesia using The Unified Theory of Acceptance and Use of Technology (UTAUT). Design/Methods/Approach: A quantitative method was applied by distributing an online questionnaire to active users of the m-health application in Greater Jakarta. The data from 242 respondents was collected through non-probability sampling techniques and analyzed by Structural Equation Modeling (SEM). Findings: The findings show that performance expectancy and price value have significant positive effects on behavioural intention. Behavioural intention significantly encourages actual usage behaviour of m-health services among consumers. Originality: This study discusses the applicability of the Unified Theory of Acceptance and Use of Technology (UTAUT) mobile health application in the Indonesian market and adds a perceived risk variable to the model to determine the influence of this variable on behavioural intention in the Indonesian context. Practical/Policy implication (optional): The findings of this research offer recommendation for m-health service providers regarding health service and the fit value of consumers.